Web engineering 11th international conference, ICWE 2011, Paphos, Cyprus, June 20-24, 2011 - Auer, Sören; Díaz, Oscar; Papadopoulos, George A. (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 11th International Conference on Web Engineering, held in Paphos, Cyprus, in June 2011. The 22 revised full papers and 15 revised poster papers presented together with 2 invited lectures were carefully reviewed and selected from 90 submissions for inclusion in the book. The papers topics cover a broad range of areas, namely, the Semantic Web, Web Services, Mashups, Web 2.0, Web quality, Web development, etc